Which factors influence the rate of failure following metal-on-metal hip arthroplasty revision surgery performed for adverse reactions to metal debris?: an analysis from the National Joint Registry for England and Wales. (August 2017) - Matharu, G. S.; Judge, A.; Pandit, H. G.; Murray, D. W.
Abstract : Aims: To determine the outcomes following revision surgery of metal-on-metal hip arthroplasties (MoMHA) performed for adverse reactions to metal debris (ARMD), and to identify factors predictive of re-revision. Patients and Methods: We performed a retrospective observational study using National Joint Registry (NJR) data on 2535 MoMHAs undergoing revision surgery for ARMD between 2008 and 2014. The outcomes studied following revision were intra-operative complications, mortality and re-revision surgery. Predictors of re-revision were identified using competing-risk regression modelling. Results: Intra-operative complications occurred in 40 revisions (1.6%). The cumulative five-year patient survival rate was 95.9% (95% confidence intervals (CI) 92.3 to 97.8). Re-revision surgery was performed in 192 hips (7.6%). The cumulative five-year implant survival rate was 89.5% (95% CI 87.3 to 91.3). Predictors of re-revision were high body mass index at revision (subhazard ratio (SHR) 1.06 per kg/m 2 increase, 95% CI 1.02 to 1.09), modular component only revisions (head and liner with or without taper adapter; SHR 2.01, 95% CI 1.19 to 3.38), ceramic-on-ceramic revision bearings (SHR 1.86, 95% CI 1.23 to 2.80), and acetabular bone grafting (SHR 2.10, 95% CI 1.43 to 3.07). These four factors remained predictive of re-revision when the missing data were imputed. Conclusion: The short-term risk of re-revision following MoMHA revision surgery performed for ARMD was comparable with that reported in the NJR following all-cause non-MoMHA revision surgery. However, the factors predictive of re-revision included those which could be modified by the surgeon, suggesting that rates of failure following ARMD revision may be reduced further. Cite this article: Bone Joint J 2017;99-B:1020–7.